Wintering birds on the island of Capri, southwestern Italy - Hjort, Christian; Andersson, Arne; Waldenström, Jonas (Ornis Svecica, 2006)
We trapped birds on the island of Capri, SW Italy, during February and earliest March 2002—2004 and in November—December 2004. The trapped birds were ringed, and common biometrical parameters measured. In total 247 birds of 17 species were trapped, a rather limited number, whereof c. 70% were either European Robins Erithacus rubecula, Blackcaps Sylvia atricapilla, Sardinian Warblers Sylvia melanocephala or Chiffchaffs Phylloscopus collybita. Although the majority of birds handled were probably settled winterers, variations in the trapping figures and cases of high body masses and fat scores suggested that in late November and December some birds may still have been en route for areas further south – and that already in late February some, particularly evident in Chiffchaffs, were on their way north again. The comparatively mild winter climate on the island of Capri may be mirrored by the lower body masses of Robins trapped by us there, compared to birds wintering on the Italian mainland which probably put on some extra fat as insurance against spells of cold weather.